Diabetic foot ulcer assessment - A comprehensive guidance for physicians - Ganesh J Shinde; Sangeetha Kalabhairav; Arun Bal; Sanjay Vaidya (Asian Journal of Medical Sciences, 2025)
Early diagnosis and a multidisciplinary team approach to manage comorbidities is essential in treating Diabetic Foot Ulcerations (DFUs). The lifetime risk of a foot ulcer in patients with diabetes mellitus (DM) is high. DFUs are a major cause of morbidity in these patients. Infected or ischemic DFUs account for approximately 25% of all hospital stays for patients with DM. Based on data from the World Health Organization, lower extremity complications of DM are among the top ten conditions in terms of years lived with disability. Moreover, patients with DM with or without a foot ulcer have increased rates of depression. These observations illustrate the importance of prompt and appropriate treatment of DFU. The information in this review of guidelines is aimed to guide the healthcare professionals involved in the care of persons with DM and DFUs.